Sulla trasmissione vernacolare dello «Schriftencorpus» attribuito allo Ps.-Mesue: per una ricognizione delle traduzioni tra XIII e XVI secolo (Carte Romanze, 2021)
The present study analyzes the diffusion of the works attributed to the Ps.-Mesue (Canones universales, De consolatione simplicium medicinarum, Antidotarium sive Grabadin, Practica sive Grabadin), and is divided into two main sections. In a first section, it provides an overview of the main translations (Hebrew, German, English, French, Spanish) produced between the Middle Ages and the Early Modern Time, and examines the main lines of reception of the Schriftencorpus. In a second part, it focuses on the four translations («volgarizzamenti») produced in Italy between the 14th and the 15th century in Tuscany and the Veneto.